Mobility investigation of LGP-30 wheeled vehicle on peat terrain - Mohd Razali bin Md Yunos (Kulliyyah of Engineering, International Islamic University Malaysia, 2013)
This project describes a simulation model and field test to study the basic design parameters of a Low Ground Pressure (LGP-30) wheeled vehicle on Sepang peat terrain in Malaysia. The tractive performance justification of an off-road vehicle is so important that it ensures the vehicle mobility over the unprepared peat terrain. Tractive performance of (LGP-30) wheeled vehicle is investigated on the low bearing capacity moderate peat terrain in Malaysia. The simulation results showed that the vehicle sinkage is more than the critical sinkage value of 100 mm, ground contact pressure is more than 17 kN/m2 and rolling motion resistance due to terrain compaction is very often more than the tractive effort of the vehicle. The vehicle was tested on the unprepared moderate peat terrain after increasing the tire-terrain interfaced by decreasing the tire inflation pressure of 5%, 10% and 15% respectively. The vehicle was found to traverse on the terrain smoothly when the tire inflation pressure was decreased by 15%. It is thus concluded that the vehicle would not be suitable to traverse on the peat terrain at other inflation pressure. Finally, some suggestions were made on the design optimization as well as recommendation for operation-wise approaches.